Lifestyle management to prevent and treat atrial fibrillation. (2nd July 2016) - Gallagher, Celine; Hendriks, Jeroen M. L.; Mahajan, Rajiv; Middeldorp, Melissa E.; Elliott, Adrian D.; Pathak, Rajeev K.; Sanders, Prashanthan; Lau, Dennis H.
ABSTRACT: Introduction: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia with a one in four lifetime risk in adults over the age of forty. Traditionally, AF management has focused on the three pillars of rate control, rhythm control and appropriate anticoagulation to reduce stroke risk. More recently, the importance of cardiovascular risk factor management in AF has emerged as a fourth and essential pillar with improved patient outcomes. Areas covered: Here, we aim to summarize the current available evidence for the association between various modifiable risk factors and AF, and to identify optimal treatment targets to improve outcomes. Expert Commentary: Care for AF patients utilizing an integrated approach and aggressive lifestyle management may reduce the enormous burden of this arrhythmia.